(untitled) (Communications in Computational Physics, 2012)
We simulate the particle transport in a thin film deposition process made by PVD (physical vapor deposition) and present several models for projectile and target collisions in order to compute the mean free path and the differential cross section (angular distribution of scattered projectiles) of the scattering process. A detailed description of collision models is of the highest importance in Monte Carlo simulations of high power impulse magnetron sputtering and DC sputtering. We derive an equation for the mean free path for arbitrary interactions (cross sections) that includes the relative velocity between the particles. We apply our results to two major interaction models: hard sphere interaction & screened Coulomb interaction. Both types of interaction separate DC sputtering from HIPIMS.